2021
DOI: 10.3389/fonc.2021.744956
|View full text |Cite|
|
Sign up to set email alerts
|

A Real-World, Multicenter, Observational Retrospective Study of Durvalumab After Concomitant or Sequential Chemoradiation for Unresectable Stage III Non-Small Cell Lung Cancer

Abstract: IntroductionFor unresectable stage III non-small cell lung cancer (NSCLC), the standard therapy consists of chemoradiotherapy (CRT) followed by durvalumab maintenance for responding patients. The present study reports on the safety and outcome of durvalumab use after CRT in a real-world, multicenter, retrospective cohort.MethodsTwo hundred thirty-eight patients have been included. We collected data on systemic therapy, radiation therapy, the timing between CRT and durvalumab, number of durvalumab cycles, reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 9 publications
1
23
1
Order By: Relevance
“…This study also showed the need to be cautious in the reirradiation of stage 7 lymph nodes due to the risk of lethal toxicity (three patients) in consideration of the risk of necrosis or fistula of the airways, as also described in a case report [ 46 ].…”
Section: Discussionmentioning
confidence: 52%
“…This study also showed the need to be cautious in the reirradiation of stage 7 lymph nodes due to the risk of lethal toxicity (three patients) in consideration of the risk of necrosis or fistula of the airways, as also described in a case report [ 46 ].…”
Section: Discussionmentioning
confidence: 52%
“…14,15,28 The outcomes from PACIFIC-R align with other realworld studies of the PACIFIC regimen. [29][30][31][32][33] For instance, Taugner et al 30 reported a rwPFS rate of 62% at 12 months with durvalumab in their prospective study, which is consistent with the corresponding rate from PACIFIC-R. Moreover, outcomes for most of the analyzed subgroups from PACIFIC-R compare favorably with patients who received CRT alone in the preimmunotherapy era 25,34 ; in the international KINDLE study, median rwPFS was 12.1 and 10.4 months with cCRT and sCRT (without consolidation immunotherapy), respectively, among patients with unresectable, stage III NSCLC (acknowledging that the index date was the date of initial diagnosis for KINDLE, whereas it was the date that durvalumab was started within the EAP [i.e., post-CRT] in PACIFIC-R).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the results of a phase III randomized Pacific trial on patients with unresectable locally advanced non-small-cell lung cancer (NSCLC) submitted to chemoradiotherapy (CHT-RT) followed by consolidative immunotherapy (IO) confirmed a significant benefit in terms of long-term clinical outcomes, as reported in the update analysis from Spiegel et al [1]. Furthermore, several observational studies involving large populations obtained similar results in real-world settings underlying the crucial role of this new multimodal approach in stage III NSCLC patients who have not progressed after radical chemotherapy (CHT) and radiotherapy (RT) [2]. Five-year survival outcomes from the Pacific trial showed a median overall survival (OS) and progression free survival (PFS) equal to 47.5 and 16.9 months, respectively, but, unfortunately, 6.3% of the patients developed brain metastasis during or after the consolidation phase with durvalumab [3].…”
Section: Introductionmentioning
confidence: 58%